Differential activity of wheat antioxidant defense system and alterations in the accumulation of osmolytes at different developmental stages as influenced by marigold (Tagetes erecta L.) leachates - Mir, Rayees Ahmad; Argal, Surendra; Ahanger, Mohammad Abass; Jatav, Keshav Singh; Agarwal, Rajiv Mohan (Frontiers in Plant Science, 2022)
Experiments were conducted to evaluate the effectivity of Tagetes erecta L. leachates on various growth, physiological, and biochemical parameters of wheat at different stages of growth. Results suggested that Triticum aestivum L. seedlings/plants when exposed to higher concentrations of marigold leachates (10%, 20%, and 30% w/v of fresh parts and 5% and 10% w/v of dry parts) exhibited enhanced lipid peroxidation along with an increase in the activity of protease and phenylalanine ammonia lyase. Treatment with higher concentrations of leachates of fresh (30% w/v) and dry (10% w/v) T. erecta upregulated the activity of superoxide dismutase, catalase, ascorbate peroxidase, guaiacol peroxidase, glutathione S-transferase, and glutathione reductase and also increased the non-enzymatic components of antioxidant defense such as glutathione, ascorbic acid, and total phenols along with osmotic constituents comprising free proline, free sugars, and free amino acids in wheat. The growth and yield attributes of wheat exhibited a slight increase at treatments with lower concentrations (1% w/v) of dry leachates, whereas a decrease was recorded at higher concentrations (10% w/v). In general, treatments with flower leachates (higher concentrations) showed greater influence as compared with those with leaf leachates. Identification and understanding the mechanism of function of allelochemicals in these leachates may pave a way for further experimentation on Tagetes erecta L crop while it is cultivated and decomposed in the field.